Virulence Mechanisms of Mycobacterium abscessus: Current Knowledge and Implications for Vaccine Design - Ferrell, Kia C.; Johansen, Matt D.; Triccas, James A.; Counoupas, Claudio (Frontiers in Microbiology, 2022)
Mycobacterium abscessus is a member of the non-tuberculous mycobacteria (NTM) group, responsible for chronic infections in individuals with cystic fibrosis (CF) or those otherwise immunocompromised. While viewed traditionally as an opportunistic pathogen, increasing research into M. abscessus in recent years has highlighted its continued evolution into a true pathogen. This is demonstrated through an extensive collection of virulence factors (VFs) possessed by this organism which facilitate survival within the host, particularly in the harsh environment of the CF lung. These include VFs resembling those of other Mycobacteria, and non-mycobacterial VFs , all of which make a notable contribution in shaping M. abscessus interaction with the host. M. abscessus continued acquisition of VFs is cause for concern and highlights the need for novel vaccination strategies to combat this pathogen. An effective M. abscessus vaccine must be suitably designed for target populations (i.e. individuals with CF) and incorporate current knowledge on immune correlates of protection against M. abscessus infection. Vaccination strategies must also build upon lessons learned from ongoing efforts to develop novel vaccines for other pathogens, particularly Mycobacterium tuberculosis (M. tb); decades of research into M. tb has provided insight into unconventional and innovative vaccine approaches that may be applied to M. abscessus. Continued research into M. abscessus pathogenesis will be critical for the future development of safe and effective vaccines and therapeutics to reduce global incidence of this emerging pathogen.